Ambient Mass Spectrometry in Imaging and Profiling of Single Cells: An Overview - Bharath Sampath Kumar (Mass spectrometry letters, 2023)
It is becoming more and more clear that each cell, even those of the same type, has a unique identity. This sophistica- tion and the diversity of cell types in tissue are what are pushing the necessity for spatially distributed omics at the single-cell (SC) level. Single-cell chemical assessment, which also provides considerable insight into biological, clinical, pharmacody- namic, pathological, and toxicity studies, is crucial to the investigation of cellular omics (genomics, metabolomics, etc.). Mass spectrometry (MS) as a tool to image and profile single cells and subcellular organelles facilitates novel technical expertise for biochemical and biomedical research, such as assessing the intracellular distribution of drugs and the biochemical diversity of cellular populations. It has been illustrated that ambient mass spectrometry (AMS) is a valuable tool for the rapid, straightfor- ward, and simple analysis of cellular and sub-cellular constituents and metabolites in their native state. This short review exam- ines the advances in ambient mass spectrometry (AMS) and ambient mass spectrometry imaging (AMSI) on single-cell analysis that have been authored in recent years. The discussion also touches on typical single-cell AMS assessments and implementa- tions. KCI Citation Count: 0